Comparative study of multilayered nanostructures for enhanced solar optical absorption. Issue 13 (2016) - Dahal, Pabitra; Chou, Jeffrey; Wang, Yu; Kim, Sang Gook; Viegas, Jaime
ABSTRACT: Improved solar spectrum optical absorption in multilayered nanostructures consisting of metal, semiconductor and dielectric layers increase their potential for efficient photon to electron conversion. In this work, we analyze the influence of different nanostructure shapes and dimensions on the optical absorption in the vacuum wavelength range of 400 nm to 1500 nm based on Finite Domain Time Difference (FDTD) method. A periodic metallic photonic crystal composed of nanorods of gold, titanium oxide, and alumina is proposed by optimizing thickness of Au and TiO2, aspect ratio, sidewall angle, and geometry of the elemental shape. A high aspect ratio structure consisting of elliptical nose cone elements with optimized dimensions is seen to absorb more than 90% of the solar spectrum in the range considered.